Reforming regional-local finance in Russia - Martinez-Vazquez, Jorge (WBI learning resources series., 2006)
The exposition is based on an analytical framework covering all?building blocks? of fiscal federalism: size and structure of jurisdictions, expenditures, revenues, transfers, and borrowing. The application of this framework to Russian settings results in a comprehensive assessment of the state of intergovernmental fiscal relations in Russia.